Imagining the “enemy”: adversarial roles in the fiction of Rabindranath Tagore and Saul Bellow, two Nobel Laureates - Quayum, Mohammad Abdul (2015)
R.K. Narayan, a pioneer of South Asian fiction in English, once argued that the underlying objective of every Indian story is to create a “distinction between good and evil” and show that “goodness triumphs in the end… if not immediately, at least in a thousand years; if not in this world, at least in other worlds.” This literary trend of pitting “good” against “evil,” or creating an adversary for the protagonist who (s)he eventually defeats in a palpable or impalpable form, is not just an aspect of South Asian imagination, but a core ingredient of the human consciousness, as is evident in the pervasive duality of God/Satan, truth/falsehood, papa/punya, in all the major global religions. In this paper, I wish to examine the various representations of the adversary or “enemy” in selected fiction of two Nobel Laureates from two different historical periods and cultural backgrounds, Rabindranath Tagore (1861-1941) and Saul Bellow (1915-2005). My contention is that, despite his reputation as a religious and mystical writer, Tagore often portrays the unscrupulous agents of decadent socio-cultural-religious practices as the “enemy” in his fiction, while Bellow, often categorised as a post-modern and existentialist writer, habitually sees the enemy in modern materialism and its temptations that stand in the way of soul’s quest for self-fulfilment and freedom.